Crocodiles yawn to keep cool - Petty, Kate.; Field, James, 1959-; Moore, Jo (Brookfield, Conn. : Cooper Beech Books, 1998)
Distinguishes between crocodiles and alligators and discusses their habitats, feeding habits, hunting behavior, reproduction, and hibernation.
Includes index.
Keywords: Crocodiles -- Juvenile literature; Alligators -- Juvenile literature; Crocodiles; Alligators